2010
DOI: 10.1095/biolreprod.109.082867
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Marrow-Derived Human Mesenchymal Stem Cell: Potential Progenitor of the Endometrial Stromal Fibroblast1

Abstract: The cellular sources that contribute to the renewal of human endometrium are largely unknown. It has been suggested that endometrial stem cells originate from bone marrow-derived mesenchymal stem cells (MSC), with subsequent development into endometrial stromal fibroblasts (hESF). We hypothesized that if bone marrow-derived MSC contribute to endometrial regeneration and are progenitors of hESF, their treatment with agents known to regulate hESF differentiation could promote their differentiation down the strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 58 publications
4
56
0
Order By: Relevance
“…The literature suggests that myofibroblasts arise from activation of resident lung fibroblasts, from differentiation of bone-marrowederived stromal cells and also from ATII cells via EMT. 1,37,38 Other reports suggest increased expression of mesenchymal marker proteins and mRNAs by hyperplastic ATII cells in human IPF lungs 4 and that approximately 30% to 50% of fibroblasts are also derived via EMT in BLM-induced lung injury. 11 This supports the importance of transformation of ATII cells into myofibroblasts via EMT in the pathogenesis of PF 12 in addition to apoptosis of ATII cells.…”
Section: Upa-fibrinolytic System In Atii Cell Emtmentioning
confidence: 99%
“…The literature suggests that myofibroblasts arise from activation of resident lung fibroblasts, from differentiation of bone-marrowederived stromal cells and also from ATII cells via EMT. 1,37,38 Other reports suggest increased expression of mesenchymal marker proteins and mRNAs by hyperplastic ATII cells in human IPF lungs 4 and that approximately 30% to 50% of fibroblasts are also derived via EMT in BLM-induced lung injury. 11 This supports the importance of transformation of ATII cells into myofibroblasts via EMT in the pathogenesis of PF 12 in addition to apoptosis of ATII cells.…”
Section: Upa-fibrinolytic System In Atii Cell Emtmentioning
confidence: 99%
“…Thus, they may be a superior MSC source for clinical trials than the traditional source which is adult bone marrow. This section will focus on the isolation of MSC from amniotic fluid (Mareschi et al, 2009, Nadri and Soleimani, 2007, Roubelakis et al, 2007, the amniotic membrane (Soncini et al, 2007, Portmann-Lanz et al, 2006, Diaz-Prado et al, 2010, the chorion (chorion laeve and chorionic villi) (Soncini et al, 2007, Portmann-Lanz et al, 2006, Igura et al, 2004, Poloni et al, 2008, the decidua (Macias et al, 2010, Aghajanova et al, 2010, umbilical cord/Wharton's jelly (Mitchell et al, 2003, Reinisch et al, 2007, Petsa et al, 2009) and umbilical cord blood (Mareschi et al, 2001, Bieback et al, 2004, Romanov et al, 2003. This section will also discuss the isolation of haematopoietic stem cells from the umbilical cord blood and the application of these cells.…”
Section: Other Gestational Tissue Sources Of Mscmentioning
confidence: 99%
“…This was confirmed in mouse bone marrow transplant studies (reviewed in Gargett and Masuda (6) and Du and Taylor (43)) and in a human study of female recipients of male donor bone marrow transplants, in which male XY þ endometrial cells were identified in the non-SP rather than SP cells (47). However, human bone marrow-derived MSC can differentiate into decidualized endometrial stromal fibroblasts in vitro as shown by gene profiling (51).…”
Section: Bone Marrow-derived Stem Cells In Endometriummentioning
confidence: 73%